2019
DOI: 10.1128/aac.02414-18
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Small Molecule, ZY354, Inhibits Dental Caries-Associated Oral Biofilms

Abstract: Biofilm control is a critical approach to the better management of dental caries. Antimicrobial small molecules have shown their potential in the disruption of oral biofilm and control of dental caries. The objectives of this study were to examine the antimicrobial activity and cytotoxicity of a newly designed small-molecule compound, ZY354. ZY354 was synthesized, and its cytotoxicity was evaluated in human oral keratinocytes (HOK), human gingival epithelial cells (HGE), and macrophages (RAW) by CCK-8 assays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…CHX as a broad-spectrum antimicrobial agent can effectively inhibit most of oral microbes but with poor selectivity, which might impose adverse effects on the oral microbial ecology after long-term use ( Tokajuk et al, 2017 ; Sakaue et al, 2018 ). A multispecies biofilm model consisting of S. mutans , S. sanguinis , and S. gordonii was reported previously that could be used to evaluate the ecological impact of the tested compounds on oral biofilms ( Zhang et al, 2019 ; Yu et al, 2020 ). In the current study, although S. mutans was less sensitive to LCG-N25 (MIC = 0.5 μg/mL) relative to the other 2 streptococci (MICs = 0.125 μg/mL) in the planktonic culture, data obtained from FISH showed that treatment with LCG-N25 led to a decreased proportion of S. mutans and an elevation of other commensal streptococci within mixed biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…CHX as a broad-spectrum antimicrobial agent can effectively inhibit most of oral microbes but with poor selectivity, which might impose adverse effects on the oral microbial ecology after long-term use ( Tokajuk et al, 2017 ; Sakaue et al, 2018 ). A multispecies biofilm model consisting of S. mutans , S. sanguinis , and S. gordonii was reported previously that could be used to evaluate the ecological impact of the tested compounds on oral biofilms ( Zhang et al, 2019 ; Yu et al, 2020 ). In the current study, although S. mutans was less sensitive to LCG-N25 (MIC = 0.5 μg/mL) relative to the other 2 streptococci (MICs = 0.125 μg/mL) in the planktonic culture, data obtained from FISH showed that treatment with LCG-N25 led to a decreased proportion of S. mutans and an elevation of other commensal streptococci within mixed biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…EPS production, which directly mediates microbial adherence to a surface, forms a polymeric matrix that enhance mechanical stability of bio lm [7]. Hence, EPS is recognized as one of key virulence factors of oral bio lm in terms of caries development [37,38]. Both the CLSM and the SEM were used to assess the bio lm microstructure, the EPS production was strikingly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of II-6s against S. mutans, S. gordonii , and S. sanguinis were measured by a microdilution method in BHI as described previously [ 23 , 27 ]. The bacterial inoculum for the experiment was adjusted to 1 × 10 7 colony-forming units (CFU)/ml for S. mutans, S. gordonii , and S. sanguinis based on the optical density at 600 nm (OD 600 ) versus a CFU/ml graph of each bacterium.…”
Section: Bacterial Susceptibility Assaysmentioning
confidence: 99%
“…Antimicrobial small molecules are promising for the control of microbial biofilm due to their structural versatility, relatively low cost, and ease of control and use [21,22]. Previous studies have reported various synthetic small molecules which display moderate efficacy against cariogenic bacteria and biofilms [23][24][25]. Reasonable structural design and scientific screening are important for the development of novel antimicrobial small molecules.…”
Section: Introductionmentioning
confidence: 99%